INOVASI MEDIA PEMBELAJARAN M-LEARNING BERBASIS FLIPBOOK - Eka Ayu Hastira; Suharti Suharti; Nur Khalisah Latuconsina (IKIP Siliwangi, 2023)
This study aims to determine the quality of the mathematics learning media in the circle material at SDN 110 Borongloe which meets the valid, practical, and effective criteria. Media development refers to the stages of the ADDIE model. The research subjects were students of class VI SDN 110 Borongloe. The instruments used in the study included: validation sheets, teacher and student response questionnaires, teacher observations managing learning, student activity observations, and learning outcomes tests. The data were analyzed quantitatively by looking for the average value of the validity, practicality, and effectiveness levels. Based on the results of the study, the validation results obtained are 4.48 with a very valid category. The results of the practicality of the teacher response questionnaire are 76.6% and the student response questionnaire is 90.9%. The results of the effectiveness of the study were measured using the student activity observation sheet with the acquisition of 91.1% in the very good category, the observation sheet on the teacher's ability to manage to learn with the acquisition of 4.67 in the very good category, and the student learning outcomes test with the acquisition of learning completeness of 93%. Thus the M-Learning learning media meets product quality assessment standards.